Special educational needs and ethnicity: Issues of over- and under-representation - Strand, S; Lindsay, G; Pather, S (Department for Education and Skills, 2006)
There have been concerns for some time about the attainment and progress of children from minority ethnic groups in the UK. One specific concern has been about their overrepresentation among pupils identified as having special educational needs (SEN). This report addresses that issue but adopts a wider perspective. Because the majority of pupils are White British (about four in five pupils) they also form the majority in absolute numbers for SEN. We have therefore investigated the evidence for both over- and underrepresentation of different categories of SEN (defined as receiving support at School Action Plus or through a Statement of SEN) among different minority ethnic groups compared with the prevalence among White British pupils, the general term for which is disproportionality. Analysis of the 2005 Pupil Level Annual School Census (PLASC) data on 6.5 million pupils in maintained schools shows clear evidence of over- and under-representation of some minority ethnic groups among the SEN group in general and among certain categories of SEN. A literature review enabled us to identify possible reasons for these disproportionalities. A survey of Local Authorities and two focus groups with survey respondents provided further perspectives, including local factors impacting on disproportionality.